2004
DOI: 10.1021/bi035948v
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization Increases the Antimicrobial Activity and Selectivity of Arginine- and Tryptophan-Containing Hexapeptides

Abstract: Arginine- and tryptophan-rich motifs have been identified in antimicrobial peptides with various secondary structures. We synthesized a set of linear hexapeptides derived from the sequence AcRRWWRF-NH(2) by substitution of tryptophan (W) by tyrosine (Y) or naphthylalanine (Nal) and by replacement of arginine (R) by lysine (K) to investigate the role of cationic charge and aromatic residues in membrane activity and selectivity. A second set of corresponding head-to-tail cyclic analogues was prepared to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
165
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(179 citation statements)
references
References 55 publications
13
165
1
Order By: Relevance
“…Trp-rich AMPs preferentially bind to model membranes containing a negatively charged headgroup relative to those containing a zwitterionic headgroup (8,17,37). We recognize that the presence of multiple Trp residues does not allow for a simple interpretation of some of the spectroscopic data reported here (37).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Trp-rich AMPs preferentially bind to model membranes containing a negatively charged headgroup relative to those containing a zwitterionic headgroup (8,17,37). We recognize that the presence of multiple Trp residues does not allow for a simple interpretation of some of the spectroscopic data reported here (37).…”
Section: Discussionmentioning
confidence: 82%
“…Other studies suggest that the antimicrobial activity of peptides containing R is higher than those of peptides containing K (34,41), while peptides containing W are more potent than those with either F or Y (8,47,49). The guanidinium group of R has a more dispersed positive charge than the single amine of K, possibly enhancing electrostatic interactions between peptides and the negatively charged bacterial membrane surface (39,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dathe et al (25) reported that cyclic peptides display improved binding affinity to their cellular targets owing to minimal entropy costs for binding. Colomb et al (26) demonstrated that the use of disulfide-bridged cyclic NGR peptide led to a 10-fold increase in the efficacy of targeting to tumor sites compared to its linear analog.…”
Section: Discussionmentioning
confidence: 99%
“…A replacement of tryptophan by tyrosine or arginine by lysine preserves the structure of the peptide but changes the activity considerably [6,8]. Since these findings point to the importance of tryptophan and arginine, the next step was the change in sequence while preserving the type of amino acid side chain.…”
mentioning
confidence: 99%